Machinability of Fibre-Reinforced Plastics 2015
DOI: 10.1515/9783110292251-003
|View full text |Cite
|
Sign up to set email alerts
|

2. Rotary ultrasonic machining of CFRP composites

Abstract: Drilling is a major machining process performed for assembly purposes in CFRP composite applications. Traditional methods of drilling CFRP composites (including twist drilling and its relative methods) have many machining problems such as short tool life, poor hole quality and low machining efficiency. There are critical needs to develop time-efficient and cost-effective processes for drilling CFRP composites. Rotary ultrasonic machining (RUM) can be one of them. This chapter presents RUM of CFRP composites, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Ultrasonic vibration amplitude, one of the most important input variables in RUM, is controlled by ultrasonic power supply. Numerous studies have found that ultrasonic vibration amplitude has direct influences on almost all output variables in RUM [7,8,13,14,22,23]. Ultrasonic vibration amplitude measurement would be thus beneficial for exploring the explanations for some experimentally observed phenomena and predicting the results of output responses in RUM.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic vibration amplitude, one of the most important input variables in RUM, is controlled by ultrasonic power supply. Numerous studies have found that ultrasonic vibration amplitude has direct influences on almost all output variables in RUM [7,8,13,14,22,23]. Ultrasonic vibration amplitude measurement would be thus beneficial for exploring the explanations for some experimentally observed phenomena and predicting the results of output responses in RUM.…”
Section: Introductionmentioning
confidence: 99%